(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This research attempted by extrapolating the reasons for the standard violation in Arabic calligraphy in the explanation of the introduction to the line from Sharh Al-Shafia by Radhi Al-Din Al-Astrabadhi. This research attempted to collect the reasons that used by the commentator in explaining the violation of some vocabulary of the standard form of Arabic orthography. The research showed the comparison between the reasons of calligraphy and the reasons of other Arabic sciences, and looking at them in terms of significance, imitation and innovation, in order to reach a closer understanding of the causes of Arabic calligraphy.